Peranan Asana Dalam Anatomi Sistematik - I Gede Pasek Mancapara (Jurnal Yoga dan Kesehatan, 2018)
Psychic and physical health become a desire for everyone, it is not only in health side, desire to have proportional body gesture, strong, and charismatic are the most things that human want to have. The scientists are competing to discover the solution including the eastern scientists with their oriental characteristic. The realization of such proportional body gesture is one of the goals from systematic anatomy as a part of the body that organized by the systems and functions. Based on the structural functionalism theory by Robert Merton, in the third part of the theory (indispensability) describe that all of the aspect of human body beside the positive side however it needs for the realization of the unity inside human body with the maximal function so it brings up psychic health or physical, including proportional body gesture and to realize something that can be studied in asana philosophy. Yoga philosophy has instructions to realize physic and physical health for locomotor system, digestive system, respiratory system, nervous system, and five senses that are part of systematic anatomy. Āsana as the one of Yoga principal forms has a role in systematic anatomy, especially locomotor anatomy as the parts concerned with gestures